Pengaruh Rasio Keuangan terhadap Kinerja Keuangan PT. Kedawung Setia Industrial Tbk - Widya Ayu Utami (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to examine the effect of financial ratios on the financial performance of PT Kedawung Setia Industrial Tbk during the period 2019 to 2023. The financial ratios analyzed include the Current Ratio, Liabilities to Assets (DAR), and Liabilities to Equity (DER), while financial performance is measured using Return on Assets (ROA). The research method used is quantitative descriptive using secondary data in the form of PT KDSI's annual financial reports. The data were analyzed using multiple linear regression with the aim of determining the effect of these ratios on ROA. The research results illustrate that the Current Ratio, DAR, and DER do not have a significant effect on ROA. The Current Ratio has a positive effect on the company's liquidity but does not have a significant impact on profitability. DAR shows a negative effect on ROA but is not significant, while DER has a positive effect but is not significant on the company's profitability. Simultaneously, the three financial ratios also do not have a significant effect on financial performance as measured by ROA.